A evolução da auditoria operacional em programas de governo no Tribunal de Contas do Estado da Bahia e suas perspectivas - Albuquerque, Roberto de Freitas Tenorio de (2009)
The research is aimed at the investigation on how the performance audits were conducted by the Court of Auditors of the State of Bahia in the period from 2001 to 2007 and accessed the dimensions of: efficiency; efficacy, effectiveness, economy and equity on the implementation of government programs. The study specifically focused on the evolutionary process of audit among public management and the Court of Auditors in the country and at the Court of Auditors of the State of Bahia. The methodologies applied were described and audits conducted on social programs were analyzed. The research was based on the texts and documents produced by several Courts of Auditors in Brazil to describe the evolution of the audit process on the country as well as in the State of Bahia, during the period from 2001 to 2007. Reports produced by the Court of Auditors of the State of Bahia regarding performance audits carried out on government social programs were also used. The conclusions indicate that the performance audits conducted by the Court of Auditors of the State of Bahia represent an improvement on the audit process regarding public management. Also shows progress on the use of new audit methodologies. Regarding the issue of the audits do or not access the five dimensions, the research points to a need of improvement relatively to culture and experience of the audit staff and to the absence parameters provided by the government programs that could help to a better evaluation of those programs. The role of the Court of Auditors of Bahia each day becomes more important since the resources are few and a good audit can contribute to improve it s use in benefit of the society in need of sustainable actions, thus contributing to make the government actions provided of efficiency; efficacy, effectiveness, economy and equity